EFEKTIVITAS BIROKRASI INVESTASI DI INDONESIA: PRA DAN PASCA LAHIRNYA UNDANG-UNDANG TENTANG CIPTA KERJA - Ivan Jeremias (2022)
ABSTRACT The government's decision to use the omnibus law in drafting the Law in Job Creation is a form of follow-up to the government's will that was echoed by President Jokowi to minimize or reduce hyper-regulation. With the Omnibus Law on Job Creation, there are around 88 regulations which have been summarized and cut into one regulation. Apart from this, this thesis also provides a clear dichotomy between the different times between before the job creation law and after the job creation law. The pre-job creation law period is described as starting at the end of the 1990s until the end of September 2019. The period of intiative change is at the same time as Jokowi's speech in MPR, which includes the simplifications that are also the perfection in the form of an omnibus law, to prevent or minimize hyper regulation. Meanwhile, the post-regulation period is the period after October 20, 2020, when the Job Creation Law Act was enacted